ORGANOPHOSPHATE EXPOSURE, ASSOCIATED RISK FACTORS AND EXPOSURE RISK ASSESSMENT AMONG VEGETABLE FARMERS IN SABAH, MALAYSIA - Botinggo, Bitinsun; Awang Lukman, khamisah; Saupin, Sahipudin; Fong Tyng, Chee; Jeffree, Mohammad Saffree (Malaysian Journal of Public Health Medicine, 2021)
Uncontrolled use of pesticides in agriculture may result in increased health risks. Organophosphate (OP) pesticides are widely used among vegetable farmers to control pests and increase productivity. The aim is to determine the organophosphate exposure, associated risk factors, and exposure risk assessment among vegetable farmers in Sabah. A cross-sectional study design in Kundasang, Sabah, Malaysia. We took a blood sample from participants for blood cholinesterase concentration measurements of pesticide exposure using the rapid test kit model Lovibond AF267. A validated questionnaire was used to collect the associated risk factors of vegetable farmers. The Hazard Identification, Risk Assessment, Risk Control (HIRARC) guidelines were used for exposure risk assessment of OP exposure. The response rate was 91.1%. About 23.3% (38 out of 163) have abnormal blood cholinesterase. The significant associated risk factors were age [aOR=1.07, 95%CI (1.02,1.13)], Body Mass Index [aOR=8.60, 95%CI (2.80,26.51)], frequency of exposure a month [aOR=5.99, 95%CI (1.29,27.76)], had not attended pesticide safety training [aOR=9.08, 95%CI (2.97,27.74)], no designated pesticide storage [aOR=6.92, 95%CI (1.70,28.25)] and low practices scores on pesticide handling [aOR=6.01, 95%CI (1.97,18.36)]. The exposure risk assessment level for vegetable farmers was at low-medium risk. Organophosphate exposure among the vegetable farmers in Kundasang was higher than in other settings. The risk factors associated with organophosphate exposure were related to inadequate compliance to the standard occupational safety and health practices in agriculture. Exposure assessment revealed the opportunity for improvement by implementing the recommended control measures. Vegetable farmers need continuous support from relevant authorities. Further research is required to understand better the health risks among vegetable smallholder farmers in Sabah.